Perempuan dan Ketahanan Pangan (Rumah Tangga) pada Masa Revolusi - Ningsih, Widya Fitria (Jurnal Sejarah Citra Lekha, 2024)
Women were primarily responsible for food security and nutrition within their households when their husbands, fathers, and sons went off to war. However, the narratives on women and their complex relationship with food problems during the Indonesian Revolution have, for long, merely been focused on their involvement in the communal kitchen. By focusing on food governance and women’s role and experiences in food production, distribution, and consumption, this article examines (household) food security in Yogyakarta during the revolutionary period. Yogyakarta was purposefully chosen as the research site because it was the birthplace of the Indonesian women’s movement and the epicentre of the physical revolution. Yogyakarta was purposefully chosen as the research site because it was the birthplace of the Indonesian women’s movement and the epicentre of the physical revolution. The study uses historical methods to examine official documents, newspapers, and interviews within oral history. It shows that the looming food crisis during the revolution heightened awareness about national food security, prompting the development of various strategies, societal adaptation, and the resilience of women. It also reveals that the domestic roles imposed on women are indirectly a form of recognition of women as the main actors in the (household) food chain.